Standardization of Relationship of Seedling Morphological Attributes to Survival and Growth of Siris (Albizia chinensis) - Guleria, Vipan; Nayital, R.K. (Indian Journal of Agroforestry, 2020)
The experiment was laid out to study the influence of morphological parameters on survival and establishment of seedling at the out planting site. Seedlings were categorized into four diameter (<2.5, 2.5-3.5,3.5-4.5 and >4.5 mm) and top height (<10, 10-20,20-30 and >30 cm) classes and transplanted during the month of March. Seedlings having a diameter of >4.5 mm exhibited the highest survival (77.27%), diameter increment (1.55 mm) and total dry biomass (15.64 g). Whereas, the maximum height increment (14.18 cm) and number of leaves (6.25) were displayed by the seedlings under 3.5-4.5 mm diameter class. Seedlings of having <2.5 mm diameter resulted in the poorest survival, growth and biomass. Seedling height of >30 cm recorded the highest survival (71.0%) and total dry biomass (11.73 g). Whereas, the seedling having initial top height of 20-30 cm registered the maximum height increment (15.43 cm) and number of leaves (6.54) after seven months of out planting.